Implementasi Sedekah Sirri Sebagai Bentuk Filantropi Dalam Al-Qur’an - shohebul hajad; jatim jatim (STIU Al-Mujtama Pamekasan, 2022)
The discussion on philanthropy is not something new, but there have been several works in the form of books, articles and scholarly research that discuss philanthropy, but the author has not found the results of someone's research on the meaning and implementation of alms in secret as a form of philanthropy in the Qur'an, so the author needs to make a discussion regarding this theme. Starting from this problem, the author needs to examine more deeply about the implementation of alms in secret as a form of philanthropy in the Qur'an. To answer this problem, the researcher uses the thematic method, namely by discussing a certain theme thoroughly and aiming to solve the problems raised, and get a conclusion and it can be used as a guide, with the Library Research. The results of the findings of this study are a form of giving in secret and intended for the poor, as a form of philanthropy, so this gift contains a very noble value for the giver, because it can prevent the birth of showing off and wanting to be praised, as well as maintaining the dignity of the person who receives it. Keywords: alms, secret alms, philanthropy, al-Qur'an